Zinc-responsive acral hyperkeratotic dermatosis-A novel entity or a subset of some well-known dermatosis? - Arghyaprasun Ghosh; Ishad Aggarwal; Abhishek De; Ayan Samanta; Gobinda Chatterjee; Sanchaita Bala; Projna Biswas; Nidhi Chowdhary (Wolters Kluwer Medknow Publications, 2015)
Background: We are reporting a series of interesting cases, which presented to us with psoriasiform lesions distributed over the acral regions of the body. The cases are unusual because they were resistant to conventional treatment modalities like topical corticosteroids, tacrolimus and oral methotrexate but showed significant improvement on oral zinc therapy. Materials and Methods: Ten patients with characteristic clinical features of distinctive hyperkeratotic plaque in the acral areas, who were resistant to treatment by different modalities including potent topical steroids and oral methotrexate, were included for detailed investigations. A proper history was taken and relevant laboratory investigations were done which included blood count, urine, liver function, renal function, hepatitis-C virus serology and serum zinc levels. Patients were followed up every 2 weeks. Histopathological examinations of the lesional tissue were done at baseline and after 6 weeks of therapy. Patients were given oral zinc daily and no other treatment during the 6 weeks course. Results: All our patients were non-reactive to hepatitis-C. Of the ten patients only one patient (10%) showed low titer of serum zinc, another (10%) showed higher zinc level, while the rest of the patients had normal zinc level. Five of our patients had chronic renal failure, one had Grave's disease and the remaining had no associated systemic illness. Histopathology mostly showed hyperkeratosis, acanthosis, prominent granular layer, spongiosis and dermal infiltrate. After 6 weeks of follow up, all patients showed rapid and remarkable therapeutic response with zinc. Conclusions: We here report a series of patients, discernible because of their uniform clinical presentation of acral hypekeratotic plaques and in showing a noticeable response to zinc. Clinical, histopathological and laboratory investigations were done to rule out diseases of similar morphology including psoriasis, acral necrolytic erythema and lichen simplex chronicus. Authors understand that further studies with greater number cases and more detailed investigations are required to establish exact etio-pathogenesis and nomenclature of this distinct subset of patients.